Liquidity creation and bank performance of Syrian banks before and during the Syrian war - Ahmad Sahyouni; Man Wang (International Journal of Financial Studies, 2019)
This paper estimates the amount of liquidity created by Syrian banks between 2004 and 2016, and further investigates the effect of liquidity creation on bank performance, controlling for a set of bank-level, industry-level, and macroeconomic variables. The findings show bank liquidity creation improved during the pre-war period and showed positive figures, but started to decline sharply during wartime. The results also show a negative relationship between liquidity creation and bank profitability (return on assets) during wartime; however, this relationship was insignificant before the war. Finally, this study conducted robustness checks to confirm its findings.
Keywords: 330; liquidity creation; bank performance; Syria; war; instrumental variable